Metagenomics approaches for studying the human microbiome - Biniam Moges; Degisew Yinur Mengistu (All Life)
The human body harbors an extremely complex and dynamic microbial community (10-100 trillion) of bacteria, archaea, viruses, and eukaryotes. The human microbiota plays a crucial role in the environment and human health under normal circumstances; nonetheless, dysfunction of the human microbiome has been associated with illnesses ranging from inflammatory bowel disease to multidrug-resistant infections. Culture-dependent human microbial exploration approaches are inadequate for discovering the diversity, abundance, and full genetic and metabolic potential of the whole microbial ecosystem. Hence, metagenomics analysis is a powerful advanced technology for comprehensively studying human microbial composition and diversity, exploring novel and antibiotic resistance genes, microbial metabolic pathways, functional dysbiosis, and co-evolution of the microbiome with the host. Therefore, owing to the increase in human microbiome sequencing projects in healthy and diseased people worldwide, it is feasible to explore the human microbiome using a metagenomics approach. Thus, this review focuses on the advancement of metagenomics for exploring the human microbiome, human microbiome metagenomics data processing, and analysis strategies. Currently used bioinformatics tools and their approaches are also discussed in the context of human microbial metagenomics.